Vascular twin nevi. Issue 7 (27th April 2017) - Agirgol, Senay; Ozturk, Hatice Nur; Akbulut, Tugba Ozkok; Gunduzoglu, Ceyda; Koc, Leyli Kadriye; Turkoglu, Zafer
Abstract : Vascular twin nevi (VTN) are characterized by the simultaneous dermatological manifestatiton of a telangiectatic naevus close to a nevus anemicus. Nevus anemicus (NA) is a vascular anomaly characterized by localized pale patches with normal melanine and melanocyte level. According to twin spotting phenomenon crossing‐over in heterozygous somatic‐cells during mitosis results in two different offspring homozygous cells. Consequent to this mechanism, two different vascular anomalies may occur at the same region. We present a patient with VTN and NA combination which we think serves as an example for a rare twin spotting phenomenon in the literature.